Предмет: Алгебра,
автор: olesya050906
Спростіть вираз:
(3х-7)(4х+8)-12(х2 +4)
Ответы
Автор ответа:
0
12х²-56-12х²+4=0
12х² сокращается
-56+4=0
-52=0
Автор ответа:
0
(3x-7)(4x+8)-12(x2+4)=12x2 + 24x - 28x - 56 - 12( 2x+4)=
12x2 + 24 - 28x - 56 - 24x - 48 = 12x2 - 28x - 56 - 104.
Ответ:
12x2 - 28x - 56 - 104.
12x2 + 24 - 28x - 56 - 24x - 48 = 12x2 - 28x - 56 - 104.
Ответ:
12x2 - 28x - 56 - 104.
Похожие вопросы
Предмет: Алгебра,
автор: ALEHANSURENOVICH
Предмет: Русский язык,
автор: stukalovanatolij0
Предмет: Алгебра,
автор: denisgolub185
Предмет: География,
автор: melnikanna30062
Предмет: История,
автор: kris228tina